Optimizing Sustainable Hr Management Practices: Catalyst For Achieving SDGs Through Empowering Coastal Communities In Indragiri Hilir Regency - Widyawati, Widyawati; Ridwan, Muannif; Susanto, Bayu Fajar (LPPM Universitas PGRI Sumatera Barat, 2025)
Indragiri Hilir Regency, as a coastal area, faces challenges in achieving the Sustainable Development Goals (SDGs), especially in poverty alleviation (SDG 1), food security (SDG 2), decent work and economic growth (SDG 8), and marine ecosystem preservation (SDG 14). Key problems include low labor skills, lack of access to economic resources, and degradation of coastal environments. The research population includes coastal communities and business actors in Indragiri Hilir, with samples determined using the purposive sampling method. Data were collected through questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) model. The results of the study show that sustainable human resource practices have a significant effect on the empowerment of coastal communities and the achievement of the SDGs. In addition, the empowerment of coastal communities also contributes to the achievement of the SDGs, albeit with a smaller influence. The model used has proven to be valid and reliable, strengthening the role of sustainable human resources in improving the welfare of coastal communities. The practical implications of this study emphasize the importance of collaboration between governments, the private sector, and society in implementing sustainability-based policies. Skills training programs, access to financing for coastal MSMEs, and sustainable natural resource management are strategic steps to support the achievement of the SDGs in Indragiri Hilir.